Why Congestion Tolling could be good for the Consumer: The Effects of Heterogeneity in the Values of Schedule Delay and Time on the Effects of Tolling - Vincent van den Berg; Erik T. Verhoef (Tinbergen Institute, 2010)
In studying congestion tolling, it is important to account for heterogeneity in preferences of drivers, as ignoring it can bias the welfare gains. We analyse the effects of tolling, in the bottleneck model, with continuous heterogeneity in the value of time and schedule delay. The welfare gain of a time-variant toll increases with heterogeneity in the value of schedule delay. With heterogeneity, tolling makes the arrival ordering more efficient, and this lowers scheduling costs. If there is not much more heterogeneity in the value of time than in the value of schedule delay, then first-best tolling decreases the generalised price for most users. In our model, first-best tolling is not most detrimental for the lowest values of time and schedule delay: it raises prices more for users with an average value of schedule delay and a slightly larger value of time. Further, the lowest values of time are among those who gain most from a public pay-lane.
Keywords: R41; R48; H23; 330; biases in calculated welfare effects; bottleneck model; distributional effects; heterogeneity in the value of schedule delay; heterogeneity in the value of time; second-best tolls.; Bottleneck; Straßenbenutzungsgebühr; Wohlfahrtsanalyse; Verteilungswirkung; Verkehrsverhalten; Zeitpräferenz; Second Best; Theorie